Carbapenem resistance gene Ppofiling in Klebsiella pneumoniae isolated from clinical and non-clinical (water and vegetables) samples - Neha, Afra Anan; Oaishi, Shahrin Sattar (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.